Neutrophilic eccrine hidradenitis in two patients treated with BRAF inhibitors: a new cutaneous adverse event. (16th April 2017) - Herms, F.; Franck, N.; Kramkimel, N.; Fichel, F.; Delaval, L.; Laurent‐Roussel, S.; Carlotti, A.; Avril, M.‐F.
Abstract : What's already known about this topic? Cutaneous adverse events are frequent with BRAF inhibitors, including cases of neutrophilic dermatoses. Neutrophilic eccrine hidradenitis is a neutrophilic dermatosis occurring mostly in patients treated with chemotherapy for a malignant haemopathy. What does this study add? Neutrophilic eccrine hidradenitis can be added to the spectrum of neutrophilic dermatoses induced by BRAF inhibitors. Replacing one BRAF inhibitor with another is a therapeutic option, as it is not necessarily associated with a relapse of the neutrophilic eccrine hidradenitis. Linked Comment:Basu. Br J Dermatol 2017; 176:1443–1444 Summary: Neutrophilic eccrine hidradenitis (NEH) is a rare neutrophilic dermatosis, first described in patients undergoing chemotherapy for a malignant haemopathy. It has polymorphous clinical features and the association of both clinical and histological features is necessary to make a diagnosis. We report the first two cases of NEH in patients treated with a BRAF inhibitor (BRAFi), either dabrafenib or vemurafenib, for a stage IV metastatic melanoma. Disseminated erythematous plaques associated with fever and polyarthralgia occurred early after the initiation of treatment and were badly tolerated. Histological analyses confirmed the diagnosis of NEH. Symptoms disappeared a few days after the cessation of treatment and introduction of topical steroids. The replacement of one BRAFi with another is a therapeutic alternative as it is not necessarily associated with a relapse of NEH. NEH can be added to the spectrum of neutrophilic dermatoses induced by BRAFis. It occurs earlier (3–4 days) than previously described drug‐induced NEH (9–12 days) and may be an earlier stage of eccrine squamous syringometaplasia, which has already been reported in the context of BRAFi‐treated patients.